Design of a Rain Water Harvesting System at Faculty of Engineering, Technology, Applied Art and Design, Kabale University. - Nyanzi, Ibrahim (Kabale University, 2023)
Rain water harvesting is a technology used to collect,convey and storing rain water for later use from relatively clean surface such as roofs,the land surface or rock catchments. This project aimed at designing a Rain water harvesting system at Kabale Univeristy,Faculty of Engineering as the solution to overcome the problem of the intermittent water supply from the main water supply by National water and sewerage corporation in addition to high water bills at the Faculty. The methods used in this project include Reconnaissance surveying (site attending) aimed at determining rainwater harvesting components available within the area of study eg.roof material and capturing the water demand at the faculty ,Data collection and analysis ie rainfall data captured from kabale district Meteological department.and finally designing the rainwater harvesting system after having all the necessary data at hand. The design involved calculations of the catchment areas, sizing of the gutters and downpipes per each catchment area and finally sizing of an optimum storage tank where all the water captured from the catchment area was to be stored for institutional use.